Theophrastus of Eresus. - Raffa, Massimo, 1972- (Philosophia Antiqua, 2018)
Among the many subjects on which Theophrastus wrote, music is one of the most fascinating, as is testified by the sources discussed in this volume. Although scanty, the material we have-sixteen texts altogether, most of which are indirect testimonies-gives an idea of the originality and modernity of Theophrastus' thought on music, and makes us regret that we do not know more. Our philosopher conceives of music as something that originates from a movement in the soul caused by passions and comes into existence through the body. Accordingly, he is interested in performance-i.e. the way in which musical expression is brought to the listener-and its effects on the soul and the body-e.g. musical therapy.